PENGARUH JENIS ALIRAN AIR TERHADAP KARAKTERISTIK DAN SIFAT MEKANIS ANTI WASHOUT UNDERWATER CONCRETE DENGAN FAKTOR AIR SEMEN 0.35 PADA PENGECORAN DALAM AIR LAUT - Harry Kurniawan (SIGMA TEKNIKA, 2018)
At the time of casting in waterlogged areas or in concrete water must have special properties, namely the properties to maintain the quality of the concrete mix and prevent the reduction of the quality of cement paste by rinsing water or the occurrence of segregation in the concrete when pouring into the water. To achieve the quality, it is necessary to add additional material which can increase the endurance of the concrete to the water rinse, the mixing of dirt due to dirty water, and facilitate the work when foundry at aqueous or in water. With the development of technology in the concrete additives industry, to get the required concrete properties in water casting, we can add additional materials in the form of anti washout agent. In this research we will discuss the effect of using antiwasout agent 0%; 0.25%; 0.5%; 0.75%, 1% of the weight of the cement against physical properties (slump, slump flow, underwater flow, weight loss) and mechanical properties (compressive strength) in cured concrete and curing in seawater. From the results of the research, it is found that the higher the antiwasout agent pent percentage added, the lower the wasout value in fresh concrete. The highest value of compressive strength of concrete is at dosage 1% AWA.